A novel TiO2@stearic acid/chitosan coating with reversible wettability for controllable oil/water and emulsions separation. (15th March 2020) - Ren, Jinping; Tao, Furong; Liu, Libin; Wang, Xia; Cui, Yuezhi
Highlights: A pH-responsive coating was easily prepared by TiO2, chitosan and stearic acid. The water droplet bouncing occurs on the coating surface. The wettability of materials can convert to superhydrophilicity under ammonia. The superhydrophobicity of coated material can be restored by heating treatment. The materials can effectively separate the oil/water mixtures and the emulsions. Abstract: Intelligent responsive materials with switchable wettability surfaces are of great importance in the field of oil/water separation. Here, a distinctive pH-responsive bio-based oil/water separation material was prepared. A low-cost titanium dioxide (TiO2 ) and environmentally friendly chitosan (CS) were used to combine with stearic acid (SA) to form the superhydrophobic TiO2 @SA/CS coating. The coated materials (cotton fabric, sponge and filter paper) can be converted from superhydrophobicity to superhydrophilicity under ammonia treatment, and the superhydrophobicity can be restored again after heating treatment. The stimuli-responsive surface of the material was applied for the separation of oil/water/oil ternary mixtures and for the effective separation of various surfactant-stabilized water-in-oil emulsions and oil-in-water emulsions before and after wettability conversion. These results may provide a new prospect for the development of intelligent responsive oil/water separation materials with controllable wettability.